Touchless Electronic Device Control Design - Sri Kusumastuti (Politeknik Negeri Semarang, 2022)
Transmission of COVID-19 occurs between humans through droplets or splashes of body fluids containing SARS-CoV-2 particles. If a COVID-19 patient does not cover his mouth and nose when coughing or sneezing, the patient will emit droplets containing the virus. Droplets can stick to the patient's hands and surrounding items. Anyone can get the virus when shaking hands or touching items that have the virus and contracting the virus if they touch their eyes, nose, or mouth without washing their hands first. In public places such as schools, offices, and hospitals, many pieces of equipment are controlled using the help/touch of a hand. The use of equipment in public places by many vulnerable people is the cause of the rapid spread of infectious diseases. The research that will be carried out is to design and manufacture tools to control equipment without touching hands to prevent the spread of infectious diseases. The controlled equipment consists of water faucets, lights, fans, and curtains. The lights, fans, and water faucets are controlled using palm movements with the max distance from the Smart IR Switch being 11 cm. If there is palm movement within the working range of the Smart Switch IR, the solenoid valve, lights and fans will change from their previous conditions. If the initial condition is 'off' it will change to 'on' or vice versa. The curtain is controlled using palm movements with the max distance to the GP2Y0A21YK0F IR sensor being 10 cm. If there is palm movement within the working range of the GP2Y0A21YK0F IR sensor then the curtain will change from its previous condition. If the initial condition of the closed curtain changes to open or vice versa.